Analisis Implementasi Total Quality Management dalam Memperbaiki Mutu Religius Siswa - Ahmad Qodri; Idi Warsah; Nuzuar Nuzuar; Jumira Warlizasusi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Implementation of Total Quality Management at SMKIT Khoiru Ummah Rejang Lebong is carried out as an effort to ensure quality that is carried out continuously. One of them is in the religious or religious aspects of students. discussion of the results of this study focused on the SWOT analysis of the implementation of TQM in improving the religious quality of students at SMKIT Khoiru Ummah Rejang Lebong. The research activity was carried out with a descriptive qualitative approach, data was collected by interview, observation and documentation, data were analyzed by data reduction techniques, displaying data, and drawing conclusions. The results of the study show that there are things that are strengths, including leadership, school management, the environment and strong cooperation. The weaknessesincludethe teacher's ability in religious aspects and the teacher's firmness in giving warnings, directions, or punishments. Things that become opportunities include a well-known school name, the trust of the school's external customers, and cooperation from parents. Threats include the transfer of principals, the impact of technological developments and student interest in learning religion. Keywords: Analysis SWOT, Total Quality Management